Leaks and appropriations: Informal advertising in Bogota’s public space (2014)
Through observing the informal advertising, under the concept of formless (Bataille), the specific section of the Avenida Chile / Calle 72 was ran in his path for three locations in the city of Bogotá during the first half of 2013. Various manifestations were identified, in the field of advertising, who involved public space and specific dynamics attempting to blurring public areas into private spaces and vice versa. The methodology was structured in three stages: the first moment began from the concept of formless and it allowed an approach to the informal publicity, without judgment, found in their strategies and modes of action original and organic practices; a second stage of fieldwork, guided by the Situationist dynamics: photographically documented experience; and finally a phase of information analysis and interpretation and modes of action of advertising in public space, helped by four categories of formless, according to authors Rosalind Krauss and Yves Alain Bois. The experience of informal trade and its advertising, talks about the disappearance and emergence, as it plays through the boundaries of space, hurry to leave the anonymity among his ephemeral residence.